Allogeneic Hematopoietic Stem Cell Transplantation in Adult Patients with Thalassemia: A Single-Center Experience and Literature Review - Uysal, Ayse; Erkurt, Mehmet Alı; Sarıcı, Ahmet; Kuku, Irfan; Biçim, Soykan; Hidayet, Emine; Merter, Mustafa (My University, 2023)
Objective: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains the only curative treatment modality in thalassemia. Its use has been limited by age, transplant-related mortality (TRM), graft rejection, and graft versus host disease (GvHD), especially in adult patients. We aimed to present our allo-HSCT experience in adult patients with thalassemia major. Material and Method: Patients’ demographic and clinical features, donor types, resource of stem cells, conditioning regimens, GvHD prophylaxis, time to neutrophil and platelet engraftments, acute and chronic GvHD, thalassemia -free survival (TFS) and overall survival were examined. Results: The study included six patients. The median age was 21.5 (20-26) years. The median ferritin levels were 1498.4 (347.4-6992.3) pg/ml. The matched sibling donor (MSD) was used in 4 patients while matched unrelated donor (MUD) was used in 2 patients. The median time to neutrophil and platelet engraftments were 17 (15-35) and 18 (15-40) days, respectively. Acute and chronic GvHD were detected in 2 and 1 patients, respectively. The TRM was detected in 2 patients (33.3%), due to infection and acute GVHD. At a median follow-up of 28 months after transplantation, 4 (66.6%) patients were alive and TFS was achieved in 2 (33.3%) patients. Graft failure was detected in 3 (50%) patients. Conclusion: Graft rejection, TRM and GvHD limited the use of allo-HSCT, especially in adult patients. These complications were reduced by re- duced-intensity conditioning regimens and allo-HSCT should be done primarily in patients under the age of 20 years and without organ damage due to iron overload.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Hematoloji